2021
DOI: 10.1155/2021/5596090
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Administration of Abacavir and Etravirine Impairs Semen Quality and Alters Redox System and Bone Metabolism in Growing Male Wistar Rats

Abstract: Highly active antiretroviral therapy (HAART) is used in HIV-infected patients. Alongside the prolongation of patients’ life, adverse side effects associated with long-term therapy are becoming an increasing problem. Therefore, optimizing of HAART is extremely important. The study is aimed at evaluating the toxicity of abacavir and etravirine in monotherapy on the reproductive system, liver, kidneys, and bones in young, sexually mature, male rats. Thirty-six 8-week-old male Wistar rats randomized into three 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
6
1
Order By: Relevance
“…Although the combination of ABC/DTC/3TC was not bone stimulatory, ABC monotherapy increased Wnt/β-catenin signaling in osteoblasts in vitro and osteocyte-enriched bone tissue in vivo . While previous studies in Wister rats have noted increased trabecular bone mass with ABC treatment, ( 23 ) in the current study, we found no changes in BMD or microarchitecture in ABC-treated mice. The discrepancies could be explained by differences in treatment duration, 6-weeks vs 16 weeks in Matuszewska et al.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Although the combination of ABC/DTC/3TC was not bone stimulatory, ABC monotherapy increased Wnt/β-catenin signaling in osteoblasts in vitro and osteocyte-enriched bone tissue in vivo . While previous studies in Wister rats have noted increased trabecular bone mass with ABC treatment, ( 23 ) in the current study, we found no changes in BMD or microarchitecture in ABC-treated mice. The discrepancies could be explained by differences in treatment duration, 6-weeks vs 16 weeks in Matuszewska et al.…”
Section: Discussioncontrasting
confidence: 98%
“…( 36 , 37 ) However, data from preclinical models have been more mixed. For example, both Conradie et al ( 38 ) and Matuszewsaka et al ( 23 ) noted bone loss with TDF treatment in rats, but neither detected elevated bone resorption marker levels. The reason for this discrepancy is unknown but has been noted in the clinic as well, with direct tissue assessments of bone biopsies from PLWH initiating TDF-based cART showing increased osteoclast surfaces with no corresponding change in CTX levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the end of the study, the authors concluded that ETR interfered with vitamin D metabolism and oxidative stress which could potentiate infertility, however, no effects on bones in growing rats was reported. In conclusion, monitoring of vitamin D levels may be essential in patients on ETR ( Matuszewska et al, 2021 ) [E].…”
Section: Drugs Active Against Human Immunodeficiency Virus (Hiv): Non...mentioning
confidence: 99%
“…Current antiretroviral drugs are not curable and people with HIV will need to take them for the rest of their lives (Pasternak et al, 2021, Stern et al, 2021. However, the optimization of HAART, which requires long-term use, is not excluded from drug-related side effects (Matuszewska et al, 2021). HIV infection is associated with comorbidities that can be caused not only by HIV itself, but also by the toxicity of long-term use of antiretroviral therapy (ART) (Ogedengbe et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%